A Triangle Design Framework for Functional Footwear for Chinese Older Adults. (2nd January 2021) - Tian, Miao; Lei, Ye; Li*, Jun
Abstract: Well-designed functional footwear can reduce health hazards in various environments. Considering the particular needs of older adults, the design of footwear must address multifunctional demands, which requires the use of the latest technology and extensive research. Focusing on Chinese older adults, this paper proposed a triangle design framework to single out critical research functions of design. It contributes to user-centered design literature by mapping out a logical, comprehensive design flow that integrates a service platform in the framework, in addition to the foci on designers and older users. The main functions of the service platform included surveying and analyzing demand, creating an empathic experience for the designers, capturing the perceptual cognition of older adults, and evaluating the product. The users' requirements are classified according to the physiological function of older adults as well as usage scenarios. The suggested design flow is user-centered and demand-oriented, and the empathy concept is incorporated into all aspects of design. Both physical and mental health are expected to be improved to promote active aging for older adults as a result of implementing this design framework.